P04.32 Integrative analysis of DNA methylation suggests down-regulation of oncogenic pathways and reduced de-novo mutation in survival outliers of glioblastoma. (19th September 2018) - Hwang, T; Mathios, D; McDonald, K; Daris, I; Park, S; Burger, P; Kim, S; Dho, Y; Hruban, C; Bettegowda, C; Shin, J; Lim, M; et al.
Abstract: Background: The study of survival outliers of glioblastoma (GBM) can have important implications on gliomagenesis as well as in the identification of ways to alter clinical course on this almost uniformly lethal cancer type. However, current studied epigenetic and genetic signatures of the GBM outliers have failed to identify unifying criteria to characterize this unique group of patients. Material and Methods: We compared global DNA methylation patterns of IDH wild-type (IDH WT) GBM patients who lived longer than 3 years (n=17, LTS-GBM) with patients who lived less than 1 year (n=12, STS-GBM), and performed comprehensive enrichment analyses with genomic and epigenomic signatures in conjunction with available open source data. The analysis result was further validated with an independent set of 10 LTS-GBM samples. Results: We found that the genome of LTS-GBM is differentially methylated relative to STS-GBM depending on CpG density: hypermethylation near CpG islands (CGIs) and hypomethylation far from CGIs. Interestingly, these two patterns are associated with distinct signature of histone mark enrichment, and oncogenic aspects in gliomagenesis. The hypomethylation pattern at the region distant from CGI is associated with H3K9me3 enrichment and lower rates of de novo mutations, while the hypermethylation at CGIs is associated with H3K27ac and correlates with transcriptional downregulation of genes involved in cancer progression pathways. Conclusion: These results extend our understanding of DNA methylation of survival outliers in glioblastoma in a genome-wide level and provide insight on the potential impact of DNA hypomethylation in cancer genome.